Vida e memória: o percurso de uma educadora quilombola - MACIEL, Maria Palmira Rodrigues (2024)
The present training memorial exposes the itinerary of Life and Memory of Maria Palmira Rodrigues Maciel, where it was sought to highlight the most relevant facts and events of the construction of student and professional life, from the beginning in the preschool to the entrance to the Federal University of Pará (UFPA), in the course of Full Degree in Pedagogy, this event being the culmination of the realization of the dream to reach the academic formation. It is highlighted among other things the personal and professional experiences experienced in the long process of knowledge construction, which have become evident through pedagogical practices. They are not static descriptions or stagnant memories in space and time, but they are faithful records that through reflections on the various stages of my formation present relations with the pedagogical practice I have experienced. It is the record of learning stories and their reflections in everyday life. In this sense, the conclusion of the Pedagogy course contributed to the acquisition of the multidimensional understanding of education, which affirms that the pedagogue is under construction.